The main tendencies of integration processes in the post-soviet space - Sharapov Otabek Muradovich; Ulmasov Rahmon Ulmasovich (Indonesian Journal of Education Methods Development, 2019)
This article explores the main problems affecting on the integration and disintegration processes in the frame of the modern regional associations of the post-Soviet space. The author analyzes the main trends of these processes. The article also describes the main factors affecting on the integration and disintegration processes in the region.